Chronic Disease Management of Children Followed with Type 1 Diabetes Mellitus - Şenay Güven Baysal; Nurdan Çiftci; İsmail Dündar; Mehmet Akif Büyükavcı; Fatma Hilal Yağın; Emine Çamtosun; Derya Doğan; Ayşehan Akıncı (Galenos Yayincilik, 2023)
INTRODUCTION: With the diagnosis of chronic illness in children, a stressful period is likely to begin for both the affected child and their families. The aim of this study was to investigate the factors affecting chronic disease management by the parents of children diagnosed with type 1 diabetes mellitus (T1DM). METHODS: The sample consisted of 110 children, aged between 4-17 years and their mothers. The patients had been diagnosed with T1DM for at least one year, and had attended pediatric endocrinology outpatients or were hospitalized in a single center. First, sociodemographic information about the child with T1DM were obtained. Then, the "Family Management Measure" (FaMM) was applied. The FaMM is constructed to measure family functioning and management in families who have a child with a chronic illness. RESULTS: Paternal years of education (p=0.036), family income (p=0.008), insulin pump use (p=0.011), and time elapsed after diagnosis (p=0.048) positively affected both the management of T1DM and the child's daily life. However, presence of chronic diseases in addition to T1DM (p=0.004) negatively affected diabetes management. Higher maternal education year (p=0.013) and family income level (p=0.001) increased parental mutuality scores. However, as the time after diagnosis increased, parental mutuality scores decreased. DISCUSSION AND CONCLUSION: It is important to evaluate the child with chronic disease with a biopsychosocial approach. This approach aims to evaluate the problems of the child and his/her family who experience the disease with a holistic approach.